Edukasi Kesehatan Tentang Penyakit Diabetes Melitus Bagi Masyarakat - Joni Siagian; Wahyu Agustina; Umi Kalsum; Sinta Juli Asmara; Syahidul Haq (Jurnal Pengabdian Keperawatan Dan Kesehatan Holistik, 2025)
Diabetes mellitus is a chronic disease that occurs when the pancreas cannot produce enough insulin or when the body cannot use the insulin produced effectively. Insulin is a hormone that regulates blood sugar. This community service provides health education about diabetes mellitus for the community. This community service activity is carried out through direct observation methods to the community and door to door education. The results show that counseling can increase the knowledge of each individual Pretest 48% and Posttest 78%. It is concluded that by providing health education to the community, their knowledge will also increase. This community service activity can have an impact on improving the health of the community.